2019
DOI: 10.1121/1.5094766
|View full text |Cite
|
Sign up to set email alerts
|

Olivocochlear efferent contributions to speech-in-noise recognition across signal-to-noise ratios

Abstract: The medial olivocochlear (MOC) efferent system modifies cochlear output to aid signal detection in noise, but the precise role of efferents in speech-in-noise understanding remains unclear. The current study examined the contribution of the MOC reflex for speech recognition in noise in 30 normal-hearing young adults (27 females, mean age = 22.7 yr). The MOC reflex was assessed using contralateral inhibition of transient-evoked otoacoustic emissions. Speech-in-noise perception was evaluated using the coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…Given the time constraint, we chose the most frequently reported SNR in the literature that showed enhancement with syllables or speech. For each condition in our study, only one level for the stimulus and the ipsilateral noise was chosen, which may not have been the optimal levels for demonstrating the associations between MOC effects and central auditory processing [ 72 ]. This is particularly important given the fact that the ipsilateral noise would also be evoking the MOC reflex in the presence of considerable within- and across-subject variabilities upon contralateral acoustic stimulation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the time constraint, we chose the most frequently reported SNR in the literature that showed enhancement with syllables or speech. For each condition in our study, only one level for the stimulus and the ipsilateral noise was chosen, which may not have been the optimal levels for demonstrating the associations between MOC effects and central auditory processing [ 72 ]. This is particularly important given the fact that the ipsilateral noise would also be evoking the MOC reflex in the presence of considerable within- and across-subject variabilities upon contralateral acoustic stimulation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computational modelling as well as animal studies have shown that such reduced broad-band amplification can improve the signal-to-noise ratio of a transient signal embedded in background noise [14][15][16][17] . However, it remains debated whether the reduction of cochlear amplification through the MOCR contributes to better speech-in-noise comprehension in humans: some studies found evidence for this hypothesis [18][19][20][21][22] whereas others did not 23,24 and yet others found the opposite behaviour 25,26 .We recently demonstrated a neural mechanism for listening in noisy backgrounds that involves the extensive efferent connections between the central auditory cortex and the brainstem 27-29 . In particular, we devised a mathematical method for measuring the human brainstem response to the periodicity in the voiced parts of speech, the temporal fine structure, and showed that this subcortical response was stronger when a speaker was attended than when he or she was ignored 30,31 .…”
mentioning
confidence: 99%
“…Computational modelling as well as animal studies have shown that such reduced broad-band amplification can improve the signal-to-noise ratio of a transient signal embedded in background noise [14][15][16][17] . However, it remains debated whether the reduction of cochlear amplification through the MOCR contributes to better speech-in-noise comprehension in humans: some studies found evidence for this hypothesis [18][19][20][21][22] whereas others did not 23,24 and yet others found the opposite behaviour 25,26 .…”
mentioning
confidence: 99%
“…Nevertheless, despite the presumed benefits of MOC activation in enhancing speech-in-noise perception, it remains unclear under which listening conditions, e.g. whether listeners are actively engaged in a task, the MOC contributes to speech perception (de Boer et al, 2012; Mertes et al, 2019; Mishra and Lutman, 2014). Although it has been speculated that MOC-mediated changes in cochlear gain could enhance speech coding in background noise (Guinan, 2017), the magnitude of OAE inhibition has been reported as either increased (Giraud et al, 1997; Mishra and Lutman, 2014), reduced (de Boer et al, 2012; Harkrider and Bowers, 2009) or unaffected (Stuart and Butler, 2012; Wagner et al, 2008) in participants with improved speech-in-noise perception.…”
Section: Introductionmentioning
confidence: 99%
“…These confounding effects of auditory attention on cochlear gain could depend on factors such as task difficulty or relevance (e.g. speech vs. non-speech tasks) or even methodological differences in recording and analysing inner ear signatures such as OAEs (Mertes et al, 2019; Mishra and Lutman, 2014). To this end, the role of the MOCR in reducing cochlear gain during goal-directed hearing in normal hearing subjects (i.e.…”
Section: Introductionmentioning
confidence: 99%